PENGUJIAN PERKERASAN ASPAL PORUS DENGAN PENAMBAHAN TREAD BAN BEKAS PADA UJI MARSHALL - Sulik Anam; Herlan Pratikto (U Karst, 2018)
Tread Used Tires is a term waste from the component of the sole of an outer tire of a vehicle made of solid rubber structure. The waste is solid, not brittle (resilient) and resistant to water. From some of the definitions of the nature so that Tread used tires can be used as a media to increase the asphalt pavement component in the preparation of the following research. From the research that has been done with volumetric and Marshall parameters, asphalt pavement without the addition of used tire tread shows the calculation of VMA 17.44%, VIM 5.14%, VFB 67.27%, Stability 1217kg, Flow 3 mm, and MQ 434 kg / mm. The addition of 10% tire tread shows the calculation of VMA 16.1%, VIM 3.4%, VFB 64.82%, Stability 1145kg, Flow 3mm, and MQ 398 kg / mm. In testing the AC-BC mixture with the addition of used tire tread using the Marshall method, it was shown that the tread of used tires was suitable as an additive in porous asphalt mixes, it was based on the general specifications of Bina Marga 2010 Division 6 on road pavement. Keywords :  Asphalt, Used Tread  Tires, Marshall Tread ban bekas adalah istilah limbah dari komponen sol ban luar kendaraan yang terbuat dari struktur karet padat. Limbah tersebut padat, tidak rapuh (ulet) dan tahan air. Dari beberapa definisi sifat ban bekas tapak dapat digunakan sebagai media untuk menambah komponen aspal perkerasan dalam persiapan penelitian berikut ini. Dari penelitian yang telah dilakukan dengan parameter volumetrik dan Marshall, perkerasan aspal tanpa penambahan tapak ban bekas menunjukkan perhitungan VMA 17,44%, VIM 5,14%, VFB 67,27%, Stabilitas 1217kg, Arus 3 mm, dan MQ 434 kg / mm. Penambahan tapak ban 10% menunjukkan perhitungan VMA 16.1%, VIM 3.4%, VFB 64.82%, Stabilitas 1145kg, Flow 3mm, dan MQ 398 kg / mm. Dalam pengujian campuran AC-BC dengan penambahan tapak ban bekas menggunakan metode Marshall, ditunjukkan bahwa tapak ban bekas sesuai sebagai aditif dalam campuran aspal berpori, berdasarkan spesifikasi umum Divisi Bina Marga 2010 6 di trotoar jalan. Kata Kunci: Aspal, Tread Ban Bekas, Marshall